A STUDY ON STUDENTS IN USING QUESTION TAG OF MODAL AUXILIARY FORM AT XI GRADE OF SMA PGRI TEMBILAHAN - Rika Tri Ramadhani; Melda Yeni; Edi Ardian (Program Studi Pendidikan Bahasa Inggris, 2019)
The purpose of this research is to know the students' ability in using question tags in the modal auxiliary format eleventh grade of SMA PGRI Tembilahan. Based on the limitation of the problem, the researcher limits the problem in using question tag in modal auxiliary form just focuses on the use modal of can, could, will, would, and should. The researcher conducted a short observation to know the number of classes at the eleventh grade of SMA PGRI Tembilahan. The number of eleventh-grade students just consists of one class, namely Class A. The total of the eleventh-grade students is 20 students. The population of this research was all of the eleventh-grade students because the sample of population less than 100 the researcher used total sampling technique. The researcher used a quantitative method to get the data needed. The research instrument in this research is testing and collected by individual test scores of students where they are asked to identify and using question tags according to the instruction given with the total correct (25). So that, each correct question tag in the modal auxiliary form will be scored by 4. Based on the result of the test, the mean score of the question tag in the modal auxiliary form was 82.6. It was categorized very high level, which included in the interval 81-100. Where 14 students get in a very good score, 5 students get in a good score, 1 student gets in a moderate score and there is no get in a low and very low score. Based on that explanation above, we can conclude that the students' ability in using question tag in modal auxiliary format eleventh grade of SMA PGRI Tembilahan includes in the realm of the category nice and understanding to use question tag in modal auxiliary form.